Education: A Fundamental Right- Case Study Of Kalakeri Sangeet Vidyalay - Dr. Tejaswini B. Yakkundimath (Elementary Education Online, 2019)
On April 1, 2010, Article 21-A of the RTE Act, which includes the phrase "free and compulsory," went into force. As a Fundamental Right, this should offer children between the ages of 6 and 14 years old free, obligatory primary education. Since its founding in November 2002, Kalkeri Sangeet Vidyalaya (KSV) has made a dedicated effort to educate students from socially and economically disadvantaged homes, even prior to the actual passage of this legislation. " KSV empowers, supports, and encourages children from socially marginalized and economically disadvantaged backgrounds to realize their full potential and attain a better life. This is done through an intensive and comprehensive educational program and through the performing arts which are undertaken in a peaceful rural residential setting." reads the mission statement of this international collaboration headed by Mr. Mathieu Fortier and Ustad Hameed Khan. The organization is situated near Dharwad in Karnataka and was founded as a registered society with the following vision: " It is the fundamental right of all children to have access to education, adequate food, healthcare services and to participate in their community’s cultural life. Empowering disadvantaged children gives them the opportunity to obtain academic qualifications as well as develop their musical talents.[1]" Kalkeri Sangeet Vidyalaya (KSV) has defined its mission in line with realizing this objective. The children who fall under the Karnataka Right to Education Act Rules 2012 include those who belong to Schedule Caste, Schedule Tribe, Category I, IIA, III B, orphan, migrant, street kid, child with special needs, and child afflicted with HIV. It states that 25% of unaided schools' authorized capacity must be set aside for the purpose of admitting underprivileged students. Children in the SC and ST categories should receive 7.5% and 1.5% of these seats, respectively, while the remaining 16% of the seats should go to other categories of children from disadvantaged backgrounds, such as kids from the neighborhood's poorer parts. In this way, KSV truly helps students from underprivileged backgrounds as it gives preference to orphans and kids whose families cannot afford to provide them with a healthy diet, education, and healthcare throughout the admissions process. Since KSV does not impose tuition on its pupils, all of its students are eligible under the RTE criteria. However, the government does not provide any funding to the school. The basic data utilized in this study will be analyzed using appropriate statistical methods. This essay examines the RTE policy and suggests that the government acknowledge educational institutions that serve children from underprivileged social groups by using the case study of KSV. It also plans to offer some insightful recommendations based on the findings to improve RTE's efficacy.